Design of a Customizable Preview Feature on Clothing Website - Eddy Soeryanto Soegoto; Muhammad Ananta Hafidz; Rania Febiananda; Daniel Maruli (Universitas Komputer Indonesia, 2022)
Clothing trends that always change over time, and the tight competition in the clothing business make producers have to rack their brains so that the business they run has additional points for consumers, ranging from changes in design, use of materials, colour selection to the promotion section. The purpose of this research is to create a custom clothing feature on the website that is useful for consumers who have a special desire for the clothes they want to buy. The research method used in this research is descriptive analysis with a quantitative approach. The results show that the addition of the Custom Clothing feature can provide better clothes ordering experience on a digital platform that can be accessed through each computer. The main concept of this feature is a choice of sizes and pieces of clothing that can be chosen without thinking about stock availability. In the end, this feature is here to help consumers who have a special desire for the clothes they want to buy, so that consumers who have special desires can have clothes from that brand without thinking about stock availabilityClothing trends that always change over time, and the tight competition in the clothing business make producers have to rack their brains so that the business they run has additional points for consumers, ranging from changes in design, use of materials, colour selection to the promotion section. The purpose of this research is to create a custom clothing feature on the website that is useful for consumers who have a special desire for the clothes they want to buy. The research method used in this research is descriptive analysis with a quantitative approach. The results show that the addition of the Custom Clothing feature can provide better clothes ordering experience on a digital platform that can be accessed through each computer. The main concept of this feature is a choice of sizes and pieces of clothing that can be chosen without thinking about stock availability. In the end, this feature is here to help consumers who have a special desire for the clothes they want to buy, so that consumers who have special desires can have clothes from that brand without thinking about stock availability